Enhancing the Impact of Evidence-based Publications on K-12 ESL Teacher Practices - Abbott, Marilyn L.; Lee, Kent; Rossiter, Marian J. (Alberta Journal of Educational Research, 2017)
The reading of current research-informed publications is an essential component of teacher professional development that has the potential to lead to or reinforce the implementation of effective instructional practices. To our knowledge, no studies have examined kindergarten to grade 12 (K-12) ESL teacher engagement in professional reading related to the teaching and learning of ESL. Therefore, we conducted a survey of K-12 ESL teachers from four Canadian provinces to examine their reading practices. Results revealed that teachers mainly consulted professional newsletter articles to address classroom-related issues and indicated that key stakeholders (e.g., teachers’ associations, school districts, and school principals) do little to enhance teachers’ reading of TESL-related publications. Several recommendations to increase teacher reading engagement are included. La lecture de publications courantes fondées sur la recherche constitue une composante essentielle du développement professionnel des enseignants et une qui a le potentiel d’entrainer la mise en œuvre de pratiques pédagogiques efficaces, ou de renforcer celles-ci. Nous ne connaissons aucune étude ayant examiné l’implication des enseignants K-12 dans la lecture de revues et d’ouvrages spécialisés portant sur l’enseignement et l’apprentissage en ALS. Nous avons donc entrepris une enquête auprès d’enseignants K-12 d’ALS dans quatre provinces canadiennes pour connaitre leurs pratiques quant à la lecture. Les résultats indiquent que les enseignants consultaient surtout des articles de bulletins professionnels pour aborder des questions liées à leur pratique. Les enseignants ont également mentionné que les intervenants principaux (par ex. les associations d’enseignants, les districts scolaires et les directeurs d’école) faisaient peu pour encourager la lecture par les enseignants de publications portant sur l’ALS. Nous présentons plusieurs recommandations pour motiver les enseignants à la lecture.